2017
DOI: 10.1016/j.jjcc.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative dual antiplatelet therapy on bleeding complications in patients with acute coronary syndromes who undergo urgent coronary artery bypass grafting

Abstract: Preoperative DAPT increases the risk of CABG-related major bleeding in Japanese patients with ACS undergoing urgent CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…In a study with 322 patients by Kim et al [20] , the authors reported that there was no association between use of clopidogrel within 5 days before CABG surgery and bleeding and reoperation. Also, in a study by Nagashima et al [21] , after comparing groups in which antithrombotic treatment was stopped and not stopped at 5-7 days before CABG, the authors found similar total volumes of intraoperative bleeding and bleeding at postoperative 48 hours between them. Similarly, they stated that they did not find significant difference between drain removal times and lengths of ICU and hospital stay.…”
Section: Discussionmentioning
confidence: 93%
“…In a study with 322 patients by Kim et al [20] , the authors reported that there was no association between use of clopidogrel within 5 days before CABG surgery and bleeding and reoperation. Also, in a study by Nagashima et al [21] , after comparing groups in which antithrombotic treatment was stopped and not stopped at 5-7 days before CABG, the authors found similar total volumes of intraoperative bleeding and bleeding at postoperative 48 hours between them. Similarly, they stated that they did not find significant difference between drain removal times and lengths of ICU and hospital stay.…”
Section: Discussionmentioning
confidence: 93%
“…It challenges its suitability for DAPT patients on a more routine basis. 3 Women with lower haemoglobin levels dominated the control group, which may have inflicted our results. Post hoc analysis showed no within-group inconsistencies for sex related to postoperative blood loss or transfusion demands.…”
Section: Discussionmentioning
confidence: 95%
“…DAPT has been shown to increase the risk of postoperative bleeding. 2,3 Preventive measures include withdrawal of antiplatelet therapy in good time before surgery, which for ticagrelor is at least 3 days. 4,5 When this is not possible, treatment of bleeding complications may require platelet transfusion, plasma, fibrinogen, fibrinolytic inhibitors and recombinant factor VIIa.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, if transfusions were necessary, the amount of transfused erythrocyte units was rather high. This might be explained by the high rate of patients with DAPT at the time of surgery [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the unstable situation of AMI, the above-mentioned arguments against total arterial CABG might play an even more important role for decision-making, as patients with AMI undergoing urgent or emergent surgery would be expected to benefit from short operation times and rapid revascularization afforded by use of venous grafting. Furthermore, AMI patients are frequently administered dual antiplatelet therapy (DAPT) preoperatively, resulting in increased risk of bleeding complications [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%